2021
DOI: 10.3390/en14082323
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Sustainable Development and Renewable Energy Sources Relationship in EU Countries

Abstract: In the context of the 2030 Agenda for Sustainable Development, by adopting the EU Renewable Energy Directive and the European Green Deal, the European Union aims at an extremely ambitious goal to become climate neutral by 2050. This goal involves a massive investment plan to support this initiative, but also to reduce disparities between Member States, in order to transform the Union into a modern, resource-efficient, and competitive economy. The main objective of this paper is to investigate the sustainable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Countries that best deal with the use of renewable energy and make progress in sustainable development are Denmark, Finland, Latvia, and Sweden. Meanwhile, at the other end, there are Belgium, Cyprus, Lithuania, Luxembourg, and Malta [76].…”
Section: Renewable Energy Sources In Literature and Eu Directivesmentioning
confidence: 99%
“…Countries that best deal with the use of renewable energy and make progress in sustainable development are Denmark, Finland, Latvia, and Sweden. Meanwhile, at the other end, there are Belgium, Cyprus, Lithuania, Luxembourg, and Malta [76].…”
Section: Renewable Energy Sources In Literature and Eu Directivesmentioning
confidence: 99%
“…A comparison of the value of insolation and electricity production is shown. Using formula (1), it is possible to calculate the energy production during the year with high accuracy, without the need to use specialised software. The difference between the solar calculations from NASA's database and the PV installation design software is 24.8 kWh per year, which is a difference of 0.6%.…”
Section: Photovoltaic Installation Simulationsmentioning
confidence: 99%
“…In the case of calculations using data from measurements at the research station for 2020, the calculated annual energy produced is lower by 31.9 kWh compared to the actual data, which is a difference of 0.66%, as shown in the Figures 13 and 14. Based on the results obtained from the measurements of the amount of energy produced from a photovoltaic installation, it can be concluded that the results obtained from formula (1), it is possible to calculate the energy production during the year with high accuracy, without the need to use specialised software. The difference between the solar calculations from NASA's database and the PV installation design software is 24.8 kWh per year, which is a difference of 0.6%.…”
Section: Photovoltaic Installation Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental management strategy in organizations is based on elements such as waste prevention, the reduction of waste sources [8], the reduction of pollution and waste management [9], as well as sustainable energy management [10], use of renewable energy sources [11], reduction of greenhouse gas (e.g., CO 2 ) emissions [12], and water resources protection [13] (e.g., reduction of water losses in water supply [14]), etc. Companies should take advantage of an economy operating with higher rates of technological development, higher energy efficiency, as well as improved optimized materials [15].…”
Section: Introductionmentioning
confidence: 99%